Komunikasi Persuasi Brand Emina Dalam Kampanye Maximum Airy Protection - Kusuma, Martina; Nugrahani, Rah Utami; Pradana, Yoka (eProceedings of Management, 2024)
The Emina brand educates the public about the use of sunscreen through the Maximum Airy Protection campaign.This campaign was carried out due to the low awareness of teenagers to use sunscreen to protect themselves from UVrays. Persuasive communication in campaign practice has elements of persuasive communication which are to invite.This research aims to analyze persuasive communication in the Maximum Airy Protection campaign for the Eminabrand, specifically in the logical aspects of message design and communicator selection. The method used in thisresearch is qualitative with a case study approach. The research results show that the persuasive communication ofthe Emina Cosmetics brand in the Maximum Airy Protection campaign uses expressive logic and rhetorical logic.Expressive logic can be seen in the campaign message which focuses on the benefits of Sun Battle Emina Cosmeticsproducts, such as products that can protect the skin from UV rays optimally. Meanwhile, rhetorical logic can be seenin the rational preparation of messages using data and facts to show the benefits of Sun Battle Emina Cosmeticsproducts for teenagers. This research also found that in maintaining its credibility, Emina Cosmetics chosecommunicators by considering authority, credibility and attractiveness. The communicators consist of doctorinfluencers, beauty influencers, Nada Tarina, and Reality Club. Through the logic of message design andcommunicator selection, it shows that there is a connection in the Maximum Airy Protection campaign. Messagedesign logic that uses strong rhetorical logic needs to be supported by the selection of strong communicators toincrease validation of the persuasive communication carried out. Keywords-persuasive communication, message design logic, communicator credibility, sunscreen education.